The Effect of Salt-Processed Psoralea corylifolia on Generative Organ Targeting - Gen-hua Zhao; Cui-ping Yan; Zi-sheng Xu; Qian-qian Gao; Zhi-peng Chen; Wei-dong Li (Journal of Analytical Methods in Chemistry)
Psoralen and isopsoralen are two isomers and main effective components within Psoralea corylifolia. In order to investigate the salt-processing effect on tissue distribution characters of psoralen and isopsoralen, a sensitive and accurate ultrahigh pressure liquid chromatographic tandem mass spectrometric (UHPLC-MS/MS) method has been developed and validated for simultaneous determination of the 2 components in rats’ tissues after administration of the extracts that came from either crude or salt-processed Psoralea corylifolia L. Data displayed that both areas under the curve (AUC) of psoralen and isopsoralen from salt-processed scurfpea fruit group were significantly increased compared with that of the crude herb group, especially in heart (p<0.05), ovary, and testes (p<0.001). Though the RE and RCmax of psoralen and isopsoralen in all of the investigated organs were over 1.0, generative organs kept the maximum value. The experiment manifested that salt-processing of scurfpea fruit can increase the distribution of psoralen and isopsoralen to generative organs, heart and spleen, and the distribution of psoralen and isopsoralen to generative organs is significantly higher compared to heart and spleen (p<0.01). Results indicate that salt-processing of scurfpea fruit can significantly increase the distribution of psoralen and isopsoralen to generative organs.